Construção e aplicação de um modelo de avaliação de bem-estar para organizações baseado nos princípios da análise do comportamento - Carvalho, Daniela Cotrim Basile de (2022)
Anxiety, depression, and burnout rates are alerts for the world of work and have challenged behavior analysts not only to plan ideal work contingencies that lead to greater productivity in enterprises but that these contingencies do not harm the quality of people’s lives. In this study, well-being in the work environment is described based on the principles of behavior analysis and on variables such as satisfaction reports and experiences at work, hours worked, health, relationships in the work environment, social impact of work products, and specific social contingencies experienced by individuals. The aim is the creation and application of an assessment model of these well-being variables in the work environment. For this, an assessment was carried out with 33 employees of a small company in São Paulo, SP, Brazil, in five steps: (1) construction of a questionnaire; (2) application of the questionnaire and data analysis; (3) interviews; (4) document analysis; and (5) direct observation of target behaviors in the natural environment. The results demonstrate that the combination of the questionnaire with individual interviews enabled the identification of aversive conditions in the organizational context that impacted well-being, especially in regard to satisfaction reports and relationships in the work environment. The analysis of the company’s documents supported the identification of organizational processes to be improved, such as the structure of work positions and salaries and the performance management system. The direct observation did not bring relevant data for the analysis of aversive conditions. It is concluded that the improvement of this assessment model can help the behavior analysts to identify the conditions that interfere with the worker’s well-being and plan interventions in organizational systems that aim to improve the quality of life and relationships in the work environment